Corpus Inscriptionum Arabicarum Palaestinae addendum : squeezes in the Max van Berchem collection (Palestine, Trans-Jordan, Northern Syria) : squeezes 1-84 - Sharon, Moshe. (Handbook of Oriental Studies. Section 1 The Near and Middle East., 2007)
During his research of the Arabic inscriptions in the Middle East at the end of the 19th century, Max van Berchem collected many squeezes of inscriptions. These squeezes are stored in the archives of the Fondation Max van Berchem in Geneva. The present publication wishes to present a scholarly record of these squeezes, many of which represent inscriptions that do no longer exist. This publication is the first of, hopefully, two addenda which will constitute a full record of one of the few treasures left by the great epigrapher in his archives. For many students of Arabic epigraphy these squeezes afford the only opportunity to have a close glimpse of the originals as possible, and learn about their contents with the aid of the photographs and studies which accompany them in this volume.